Out of many, One : Portraits of America's Immigrants - Bush, George W. 1946- (George Walker) (New York : Crown Publishers, 2021)
"The issue of immigration stirs intense emotions today, as it has throughout much of American history. But what gets lost in the debates about policy are the stories of immigrants themselves, the people who are drawn to America by its promise of economic opportunity and political and religious freedom--and who strengthen our nation in countless ways. In the tradition of Portraits of Courage ... Out of Many, One brings together forty-three full-color portraits of men and women who have immigrated to the United States, alongside ... stories of the unique ways all of them are pursuing the American Dream"--
Keywords: Bush, George W -- 1946- -- Themes, motives; Immigrants -- Portraits. -- United States; Immigrants -- Biography -- United States; American Dream